Persepsi dalam Health Belief Model pada Kesadaran Risiko Kontaminasi Bakteri di Kosmetik pada Mahasiswi Tata Kecantikan UNNES - Fadiah Khairina Firamadania; Maria Krisnawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Bacterial contamination in cosmetic products is frequently overlooked, despite posing considerable health risks particularly among users who habitually share cosmetic tools. This study aims to examine both the simultaneous and partial effects of Health Belief Model (HBM)-based perceptions on awareness of bacterial contamination risk in cosmetics. Employing a descriptive-analytic cross-sectional design, the study involved 208 active female students of the Cosmetology Education Study Program at Universitas Negeri Semarang (UNNES) from the 2022–2025 cohorts, selected through simple random sampling. A Likert scale (1–5) was used to measure six HBM constructs perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy alongside risk awareness indicators. Data were analyzed using descriptive statistics, Spearman correlation, and multiple linear regression. Results indicate that all variables fall within the high category. Bivariately, all six HBM constructs demonstrated positive and significant correlations with risk awareness (r = 0.533–0.833; p < 0.001), with cues to action showing the strongest association. Multivariately, the model accounted for 93.2% of variance in risk awareness (R2 = 0.932; F = 461.241; p < 0.001). Perceived benefits emerged as the most dominant predictor (B = 0.854; p < 0.001), while perceived barriers showed no significant partial effect (p = 0.132). These findings confirm that the HBM framework is a highly reliable predictor for mapping cosmetic bacterial contamination risk awareness.